Five-factor personality structure In early adolescence - Cieciuch, Jan (Studia Psychologica: Theoria et praxis, 2010)
The article contains verification of the Five-Factor structure in early adolescence. Against recommendation of McCrae et al. (1996) it was not applied Procustes Rotation. According to psychometrie recommendation (Borsboom, 2006) we used Confirmatory Factor Analysis with items parceling (Williams, 0’Boyle, 2008). The study was conducted on 395 Polish adolescents using Big Five Questionnairefor Children of Barbaranelli, Caprara, Rabasca, Pastorelli (2003) in the Polish version of Cieciuch and Toczyłowska. The sample was divided into two subsamples. In the first one was the exploratory analysis were done and in the second one confirmatory analysis. Model fit coefficients in Confirmatory Factor Analysis are acceptable, therefore the Five-Factor structure of personality in early adolescents was confirmed.